Genetic structure of Hylarana erythraea ( Amphibia : Anura : Ranidae) from Malaysia. - Ramlah, Zainudin; Shukor, Mohd Nor; Norhayati, Ahmad; Badrul Munir, Md Zain; Mustafa, Abdul Rahman (Springer, 2010)
We studied the genetic structure and evolutionary relationships among populations of Hylarana erythraea in Sarawak, Malaysian Borneo (Borneo Heights of Padawan, Sadong Jaya, and Bario) and central Peninsular Malaysia (Tasik Chini of Pahang) using the partial cytochrome oxidase subunit 1 (CO1) gene of mitochondrial (mt)DNA. Two distinct geographical clades were observed, i) the 1st clade, haplogroup 2 included 7 divergent haplotypes in Bario, whereas ii) the 2nd clade (haplogroup 1) contained 16 haplotypes of the remaining populations. Gene flow estimators indicated high numbers of migrants per generation and panmictic populations of this species, except for a low number of migrants per generation and genetic isolation of the Bario population. The species was estimated to have undergone population expansion either for the whole population or for each population as shown by small and nonsignificant values of the sum of the standard deviation of the observed and expected mismatch distributions and Harpending raggedness index. However, multimodal distributions were seen in the scatterplot of mismatch distributions for the entire populations of Sadong and Bario. Geographical subdivision might explain the anomalies in the mismatch distribution for these populations. Furthermore, a large negative value and significant test of Fu’ Fs in the Bario population suggested recent expansion and are indicative of dispersal from ancient Sunda Shelf populations (Pahang, Sadong, and Borneo Heights) to East Sarawak (Bario). The results suggested that populations of H. erythraea were subdivided where populations in central Peninsular Malaysia and western Borneo were more closely related than those in western Borneo were to those of eastern Borneo. The study implied that a feature in the landscape of Borneo (the Lupar line) created a greater barrier than repeated intervening ocean between glacial periods. Our study also supports the notion that a widely distributed frog species includes different evolutionary lineages that are possibly cryptic species